Design of cellulose based micro- and nanostructures for encapsulation and controlled release of lipophilic biomolecules - Casanova, Francisca Casanova Cerqueira (2023)
Poor aqueous solubility, stability and bioavailability of interesting active biomolecules is a challenge in the development of bioactive formulations. Cellulose micro- and nanostructures are promising and sustainable carriers with unique features that may be used in enabling delivery strategies. In the context of sustainable development, lignocellulosic biomass from industrial and agricultural wastes have attracted much attention as cellulose sources. Sugarcane plantations for the sugar and alcohol industries are known for their high volumes and large amounts of residues, such as sugarcane bagasse (SCB), a promising renewable and low-cost source of cellulose. This PhD project aims to valorize a major by-product of the agro-industrial sugarcane industry – SCB – by extracting the cellulose polymer and developing micro- and nanostructured systems for the delivery of lipophilic biomolecules as means to offer an efficient and controlled release of these molecules and promote their biological functions. Initially, a chemical and structural characterization of SCB was performed, followed by the evaluation of different approaches for the extraction and purification of cellulose from SCB. Considering the results obtained through the different and complementary techniques employed, the most promising approach revealed to be autohydrolysis (170 ºC for 1 h), followed by bleaching with hydrogen peroxide (12%, v/v, at 85 ºC for 1.5 h) and sodium chlorite (12%, w/v, at 85 ºC for 1.5 h). Through this method we were able to obtain a white cellulose rich fraction (87.5% ± 0.6 cellulose) with low contaminants, high crystallinity index (73.1% ± 1.1) and typical cellulose functional groups from SCB. Microcrystalline cellulose (MCC), cellulose nanofibers (CNF) and cellulose nanocrystals (CNC) were then produced from the SCB cellulose rich fraction, contributing to the valorization of the agro-industrial byproduct. Optimized MCC, CNF and CNC were produced by mild acid hydrolysis, ultrasonication and acid hydrolysis followed by sonication, respectively. MCC had a particle size of ca. 30 μm, CNF of ca. 600 nm long and 8 nm wide, and CNC of ca. 120 nm long and 6 nm wide, which is in agreement with the definition of these types of structures in the literature. ATR-FT-IR and PXRD results confirm the cellulose structure for the three cellulosic materials. CNC had a higher crystalline fraction than CNF, which is attributed to the removal of the amorphous part of the microfibril during acid hydrolysis. The overall properties of our micro- and nanocellulose materials were found to be similar to those of commercial products. Subsequently micro- and nanocellulose were tested as carrier materials for the delivery of lipophilic biomolecules: curcumin, a model lipophilic biomolecule, and cannabigerol (CBG), a promising cannabinoid. Nanocellulose hydrophobic modifications with the surfactant cetyltrimethylammonium bromide (CTAB) and tannic acid/decylamine (TADA) and modification by TEMPO-mediated oxidation, were also tested and compared with the unmodified structures. The modified cellulose structures were characterized and found to successfully bind curcumin, with encapsulation efficiencies (EE) ranging from 63% to 99%. The CTAB and TADA modifications resulted in highly effective EE of 90-99% for curcumin. These modified systems provide a strategy for stabilizing and delivering curcumin by fixing it in hydrophobic domains, potentially improving its solubility and stability. Among the modifications, CNC-CTAB showed the most promising results, allowing for a sustained release of curcumin (ca. 50% released in 8 hours) and exhibiting high EE (ca. 80%) for both curcumin and CBG after scale-up by spray drying. The safety and biological potential of the CNC-CTAB delivery systems encapsulating curcumin and CBG were evaluated. In vitro cytotoxicity and genotoxicity tests were performed on the systems, which revealed to be safe for intestinal application at certain concentrations. Encapsulation reduced the cytotoxicity of both curcumin and CBG, highlighting the potential benefits of using CNC-CTAB as a delivery system for these compounds. The encapsulated biomolecules demonstrated antioxidant and anti-inflammatory properties, effectively reducing reactive oxygen species and cytokine production by intestinal cells. The delivery systems also exhibited antimicrobial properties against Campylobacter jejuni, suggesting its potential in mitigating inflammation in the gastrointestinal tract. Furthermore, the system showed ability to protect curcumin from degradation and facilitate its interaction with the intestinal epithelium, highlighting the potential of CNC-CTAB as a carrier to enhance the biological functions of curcumin and CBG, particularly in the context of intestinal inflammatory disorders. The valorization approach proposed in this work could be beneficial for the sugarcane industry to improve its environmental and economic sustainability in line with circular bioeconomy. This study emphasizes the potential of hydrophobic modified CNC as delivery systems for lipophilic biomolecules. This system effectively reduced the cytotoxicity of curcumin and CBG, protected from degradation, and enhanced biological activities, allowing for their beneficial effects to last longer and be more effective. This breakthrough has the potential to be applied to other compounds and ingredients, serving as an innovative step in utilizing agro-industrial by-products for value creation.